Evaluation of Microbiological, Physicochemical and Sensorial Properties of Purple Basil Kombucha Beverage - Seydi Yıkmış; Sergen Tuğgüm (Turkish Journal of Agriculture: Food Science and Technology)
Kombucha is a beverage prepared from fermented traditionally-flavored black or green tea (Camellia sinensis L.) with symbiotic culture of bacteria and yeast (SCOBY). In this study, the changes in the physicochemical, bioactive components, microbial quality and sensory properties of black tea kombucha and different proportions of purple basil (Ocimum basilicum L.) kombucha after fermentation were evaluated. While the pH values decreased during storage, the total acidity value increased. Purple basil had higher total phenolic content at all storage times than the other samples. At the end of the study, it was concluded that the total amount of phenolic compounds and flavonoids in purple basil was highly conserved compared to the other samples. Antioxidant values on the 30th day determined highest DPPH (radical scavenging activity) (64.19%) and CUPCAC (cupric reducing antioxidant capacity) (41.48%) in the purple basil kombucha beverage. When the color values were examined, it was found that there were statistically significant differences in the overall storage process in all samples. There was no significant change inconsistency, smell, taste and general acceptance with the storage process. As a result, 30-day storage period was found to be more successful and favorable for 100% purple basil kombucha tea.